Early Stunting Prevention Through Providing Education to Pregnant Women - Lubis , Ayu Ulfah Nur; Harahap, Seri Wahyuni; Khoiriani, Kiki (PT Inovasi Pratama Internasional, 2025)
One of the chronic nutritional problems in toddlers is stunting. Even though stunting is experienced by toddlers, it is caused by several important risk factors since pregnancy so that more attention is needed to prevent stunting since pregnancy. This study aims to analyze the effectiveness of various stunting prevention efforts since pregnancy. This research method begins by searching for articles on Google Scholar in the period 2017-2021 and using the keywords stunting prevention, stunting since pregnancy, prevention, stunting, and pregnant women. The results of the study found 4 articles on stunting prevention since pregnancy which stated that promotive and preventive efforts with various media and methods can affect the knowledge, attitudes, and practices of pregnant women regarding stunting prevention. Efforts to provide education through various methods and using various educational media can increase knowledge, attitudes, and behavior regarding stunting prevention since pregnancy.